Clinical relevance of PD-L2 expression in surgically resected lung adenocarcinoma. (June 2022) - Takamochi, Kazuya; Hara, Kieko; Hayashi, Takuo; Kohsaka, Shinji; Takahashi, Fumiyuki; Suehara, Yoshiyuki; Shimokawa, Mototsugu; Suzuki, Kenji
Highlights: PD-L2 positivity is related to adverse prognostic features in lung adenocarcinoma. PD-L2 expression is not associated with survival outcomes. PD-L2 expression shows a contrasting prognostic impact based on PD-L1 expression. PD-L2 positivity characteristics may be useful for individualized immunotherapy. Abstract: Objectives: Programmed death ligand 1 and 2 (PD-L1 and PD-L2) bind programmed death 1 (PD-1). PD-L1 is an established predictive biomarker of response to immunotherapies targeting PD-1 and PD-L1 in lung adenocarcinoma (LUAD). However, the clinical relevance of PD-L2 expression in patients with LUAD remains unclear; we aimed to examine this aspect using LUAD specimens. Materials and methods: PD-L2 expression status was immunohistochemically evaluated in 980 surgically resected LUAD specimens. PD-L2 expression status was classified based on the tumor proportion score (TPS) as negative (<1%), weakly positive (1–49%), or strongly positive (≥50%). Correlations between PD-L2 and PD-L1 expression status, clinicopathological features, driver oncogene alterations ( EGFR, KRAS, ALK, ROS1, and RET ), and prognosis were also analyzed. Results: PD-L2 expression was negative in 720 (73%) of 980 LUADs, weakly positive in 190 (19%), and strongly positive in 70 (7%). The concordance rate between PD-L1 and PD-L2 expression was 60%. Male sex, smokers, tumors > 3 cm in size, high-grade tumors, tumors without EGFR mutation or ALK fusion, and tumors with KRAS mutation were more common in patients with PD-L2-positive tumors (TPS ≥ 1%) than in patients with PD-L2-negative tumors (TPS < 1%). PD-L2 expression was not associated with overall survival (OS) or relapse-free survival (RFS). However, positive PD-L2 expression tended to be associated with better OS/RFS in PD-L1-positive patients and worse OS/RFS in PD-L1-negative patients. Conclusions: PD-L2-positive LUADs showed biologically aggressive characteristics. PD-L2 expression status was not associated with survival outcomes, but tended to show contrasting prognostic impacts based on PD-L1 expression status.